Serum Oxidative Stress Markers and Genotoxic Profile Induced by Chemotherapy in Patients with Breast Cancer: A Pilot Study. (20th October 2015) - Júnior, Antonio Luiz Gomes; Paz, Marcia Fernanda Correia Jardim; Silva, Laís Iasmin Soares da; Carvalho, Simone da Costa e Silva; Sobral, André Luiz Pinho; Machado, Kátia da Conceição; Ferreira, Paulo Michel Pinheiro; Satyal, Prabodh; Freitas, Rivelilson Mendes de; Cavalcante, Ana Amélia de Carvalho Melo
Abstract : The aim of this study was to evaluate the oxidative parameters of erythrocytes and genotoxicity in leukocytes of patients with breast cancer. Oxidative parameters were detected by spectrophotometry and genotoxic damage by single cell gel electrophoresis. Twenty-eight women with breast cancer were monitored before chemotherapy and after the second and fourth cycles of therapy with cyclophosphamide and doxorubicin. After the fourth cycle, increases (P < 0.05 ) in the reactive substances to thiobarbituric acid levels, nitrite content, and superoxide dismutase activity and high rates of DNA damage in leukocytes were observed when compared with healthy women group and baseline levels. Similarly, after the second cycle, the same parameters were increased (P < 0.05 ) when compared with baseline levels. Increase in catalase activity was detected only after the fourth cycle and reduced glutathione levels and glutathione peroxidase activity were decreased in all cycles when compared with healthy women, as well as after the second and fourth chemotherapy cycles compared to baseline (P < 0.05 ). Patients with breast cancer presented an indicative of oxidative stress before, during, and after chemotherapy, as well as increased genotoxic damage in all stages of treatment, demonstrating the clinical applicability of this investigation.